Wells Syndrome Successfully Treated with Tripterygium Glycosides - Lu J; Wu W; Zhang M; Wang P; Niu M; Yang X (Dove Medical Press, 2021)
Jiejie Lu, Weiwei Wu, Ming Zhang, Ping Wang, Mu Niu, Xianxu Yang Department of Dermatology, The Fifth People's Hospital of Hainan Province, Branch of National Clinical Research Center for Skin and Immune Disease, Haikou, Hainan, People's Republic of ChinaCorrespondence: Mu Niu; Xianxu YangDepartment of Dermatology, The Fifth People's Hospital of Hainan Province, Branch of National Clinical Research Center for Skin and Immune Disease, No. 33, Southern Road of Longkun, Qiongshan District, Haikou, 570206, Hainan, People's Republic of ChinaTel +86-18389485160; +86-13876300372Fax +86-898-66729550; +86-898-66729550Email 382219948@qq.com; 13876300372@139.comAbstract: Wells syndrome (WS), also known as eosinophilic cellulitis, is a rare inflammatory dermatosis of unknown etiology that typically presents with pruritic cellulitis-like plaques. The first line treatment options for WS are topical or systemic corticosteroids, however, the development of side effects of systemic corticosteroids usually led to a switch to the second line therapy. Here, we reported a rare case of facial Wells syndrome misdiagnosed with bacterial cellulitis. A 26-year-old female presented with a one-week history of erythematous, edematous and blushing plaques partially covered by bullae. A skin biopsy revealed diffuse infiltration of eosinophils in the entire dermis and "flame figures" compatible with WS. Initially, the patient was successfully treated with methylprednisolone. However, three month later, the disease relapsed. Because of weight gain and centripetal obesity, the patient refused to oral administration of methylprednisolone. Traditional Chinese Medicine tripterygium glycosides (TG) 60mg/day was prescribed and the lesions completely resolved after 4 weeks without any recurrence. Our case suggests that tripterygium glycosides may be a safe and effective treatment option for Wells syndrome.Keywords: Wells syndrome, tripterygium glycosides, facial cellulitis